College Algebra 7th Edition

Published by Brooks Cole
ISBN 10: 1305115546
ISBN 13: 978-1-30511-554-5

Chapter P, Prerequisites - Chapter P Review - Exercises - Page 77: 71



Work Step by Step

Square the binomial using the formula $(a-b)^2=a^2-2ab+b^2$ with $a=x$ and $b=2$ to obtain: $=x^2(x-2)+x[x^2-2(x)(2) + 2^2] \\=x^2(x-2)+x(x^2-4x+4)$ Distribute $x^2$ and $x$ to obtain: $=x^2(x) -x^2(2) + x(x^2) -x(4x)+x(4) \\=x^3-2x^2+x^3-4x^2+4x$ Combine like terms to obtain: $=(x^3+x^3) + (-2x^2-4x^2) + 4x \\=2x^3-6x^2+4x$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.